Inflammatory Myeloradiculitis Secondary to Pembrolizumab: A Case Report and Literature Review. (18th August 2020) - Vickers, M. L.; Seidl, B.; Bigby, K.; Chern, B.; Eriksson, L.; Hartnett, G.; Gericke, C.; Chew, R.
Abstract : Immune checkpoint inhibitors are the most important new medications in oncology and include inhibitors of programmed cell death protein-1 (PD-1) such as Pembrolizumab, Nivolumab, and Cemiplimab. These anticancer agents prevent tumour immune evasion and have been associated with a range of immune-related adverse events (irAEs) including those involving the nervous system. In this case report and literature review, we present the first case of inflammatory myeloradiculitis secondary to Pembrolizumab. We also summarise the characteristics, treatment, and outcomes of other cases reported in the literature which include a component of myelitis. Finally, we make general recommendations on management.